Konsep Pendidikan Islam Perspektif KH. Hasyim Asy’ari dan KH. Ahmad Dahlan - Suadi; Hamdan Robbani (Universitas Nahdlatul Ulama Pasuruan, Indonesia, 2023)
Islamic education is basically a step in the right direction. This improvement, which has occurred since the Prophet Muhammad SAW lived until recently, was the result of completed direction from Allah. Numerous Muslim academic experts have focused their attention on Islamic education and have produced numerous publications in this area. K.H. Ahmad Dahlan placed Muslims at the center of science, while K.H. Hasyim Asy`ari prioritized religious education over general education. K.H. Ahmad Dahlan presented two ideas regarding the outcomes of Islamic education: the creation of intellectual ulama and the intellectual ulama itself. According to K.H. Hasyim Asy`ari and K.H. Ahmad Dahlan, the idea of Islamic education is highly helpful in expanding Islamic education in this nation and can result in Muslims who are whole and true to their nature. Furthermore, it is a very good idea to implement in this country since the concept they developed can help shape a progressive society or pupils who can meet the problems of this globalized period